Preparation process of rock plate with clear granular sensation
By adding mullite and using powder modifiers, the problem of insufficient density of the internal structure of the rock slab is solved, the compressive strength and thermal stability are improved, the surface particle size is maintained, and the market attractiveness is enhanced .
Patent Information
- Application Number
- CN202411314611.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
Due to the internal structure of the existing rock slabs, they are prone to wear after long-term use, resulting in insufficient surface graininess and clarity, affecting aesthetics and market attractiveness.
Using a process of increasing mullite content, the moisture and particle size of the powder are optimized through spray drying and the use of powder modifiers, the clarity and fineness of the particle feel are improved, and the crystallization and fineness of the particle feel are increased, and the multi-stage temperature-controlled drying kiln and high-temperature firing is sintered. Control temperature and time during the process to ensure the stability of the physical properties of the rock slabs.
It improves the compressive strength and thermal stability of the rock slabs, maintains the clarity of surface particle size, and enhances the market attractiveness and adaptability to the use environment.
Smart Images

Figure CN119191816A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rock slab preparation, and specifically to a process for preparing a rock slab with clear granularity. Background Art
[0002] As a new type of building decoration material, rock board is favored by the market for its superior physical properties, rich colors and wide range of applications. It has shown unique advantages in home decoration, kitchen board, furniture making and high-end architectural space.
[0003] After searching, China's public authorization number CN115677325B discloses a preparation process of a ceramic rock plate with clear granularity and a ceramic rock plate thereof, which belongs to the field of ceramic rock plate production. The preparation process includes the following steps: (1) ball milling powder: ball milling the base powder and spot powder of different colors into slurry according to the formula ratio, and aging for more than 48 hours; (2) spray drying: supplying the slurry into the spray drying tower for spray drying, and the powder passes through a 30-mesh drum screen; (3) mixing: adding the powder into the drum screen, first passing through a 60-mesh drum screen, and then passing through a 100-mesh drum screen for mixing; (4) pressing: before entering the press, the powder passes through a 50-mesh screen and then pressed; (5) drying: (6) firing and post-treatment: obtaining a ceramic rock plate with clear granularity. Compared with the existing ceramic rock plate with a size of about 30 mesh spots throughout the body, the ceramic rock plate prepared by the present invention has a finer texture of spots throughout the body and a clearer granularity, which can meet the needs of higher-end home decoration.
[0004] During the long-term use of existing stone slabs, due to the insufficient density of the internal structure, the stone slabs are more easily worn after long-term use, resulting in insufficient surface graininess and clarity of the stone slabs, which in turn affects the product's aesthetics and market appeal. Summary of the invention
[0005] The purpose of the present invention is to provide a process for preparing rock slabs with clear graininess in order to solve the problem that, during the long-term use of existing rock slabs, the rock slabs are more easily worn due to their insufficiently dense internal structure, resulting in insufficient surface graininess and clarity of the rock slabs, thereby affecting the aesthetics and market appeal of the product.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention is a process for preparing a rock plate with clear granularity, comprising:
[0008] S1. Raw material preparation: transport the mud, mullite, water-abrasive, green body toughening material, recycled material and additives required for the production of rock slabs to the required location according to the proportion;
[0009] S2, ball-milled powder: ball-mill the base powder and the spotted powder into slurry according to the formula ratio, and the slurry needs to be aged for more than 48 hours;
[0010] S3, spray drying: The aged green body slurry and spot slurry in the slurry pool are respectively supplied to the spray drying tower through the spray tower slurry pump. The spray drying process requires controlling the spray plate aperture and swirl plate thickness of the spray gun head, and maintaining the temperature in the spray tower to optimize the moisture content and particle size of the powder;
[0011] S4, powder mixing: the spotted powder and the base powder are evenly dispersed, and a powder modifier is added during the mixing process, thereby improving the clarity and fineness of the granularity;
[0012] S5, compression molding: the mixed green body powder is passed through a sieve to ensure that the particle size is uniform and then sent into a press for compression;
[0013] S6, green body drying: the green body after pressing and forming is transported to the drying kiln for drying;
[0014] S7, firing and forming: the dried green body is sent to the calcining kiln for firing.
[0015] Further, in S1, the clay, mullite, abrasive, body toughening material, recycled material and additive are prepared from the following components in parts by weight: 35-46.1 parts of clay, 50-60 parts of abrasive, 1-7 parts of body toughening material, 0.5-3 parts of recycled material; 0.1-0.8 parts of additive
[0016] The ratio of the mud material to mullite is 1:0.5;
[0017] The water-abrasive material is prepared from the following components in parts by weight: 7.4 parts of water-washed potassium-sodium stone particles, 8.3 parts of water-ground sodium stone powder, 33.3 parts of water-ground medium-temperature sand, 3.7 parts of mortar recycling material, and 47.3 parts of water-ground high-temperature sand;
[0018] The additive is prepared from the following components in parts by weight: 16.1 parts of modified lignin, 48.4 parts of modified bentonite, 32.3 parts of polyvinyl alcohol rubber solution, and 3.2 parts of carboxyl cellulose and acrylate copolymer liquid enhancer.
[0019] Furthermore, in S3, the moisture content of the powder is controlled at 5.5-6.5%, and the outlet temperature needs to be lower than 80°C.
[0020] Further, in S4, the powder is first passed through a 60-mesh and then a 100-mesh drum screen to ensure uniform mixing.
[0021] Furthermore, in S4, a powder modifier is added during the mixing process to improve the clarity and fineness of the granularity.
[0022] Further, in S5, the mixed green body powder is passed through a 50-mesh sieve, screened, and sent to a press for pressing and molding. The pressure of the press is 550-560 kg / cm 2 , speed is 11.5 times / minute.
[0023] Furthermore, in S6, a multi-stage temperature-controlled drying kiln is used, with the first four zones at 180°C, the front three zones at 160-170°C, the middle three zones at 135-150°C, and the last three zones at 120°C.
[0024] Furthermore, in S6, the residual moisture of the green body is adjusted to be less than 0.5%, and the dry strength WEI of the green body is 3.5-4.5 MPa.
[0025] Furthermore, in S7, the firing temperature is controlled within a range of 1178 to 1193°C, the high-fire holding time is controlled within a range of 8 to 12 minutes, and the firing time is controlled within a range of 120 to 170 minutes.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] By increasing the content of mullite, the compressive strength of the rock slab is also improved accordingly, which helps to maintain the integrity of the rock slab surface and reduce the particle size blurring caused by wear. Mullite has a low thermal expansion coefficient and excellent thermal shock stability, so that the rock slab containing mullite can still maintain stable physical properties in high temperature environments, which helps to maintain the clarity of the particle size on the surface of the rock slab in an environment with large temperature changes, and prevent particle size changes or blurring caused by temperature fluctuations, thereby increasing the attractiveness of the rock slab in the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a specific flow chart of the present invention. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0030] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0031] The present invention provides a process for preparing a rock plate with clear granularity, comprising the following steps:
[0032] S1. Raw material preparation: transport the mud, mullite, water-abrasive, green body toughening material, recycled material and additives required for the production of rock slabs to the required location according to the proportion;
[0033] As a further embodiment, the clay, mullite, abrasive, body toughening material, recycled material and additive are prepared from the following components in parts by weight: 35-46.1 parts of clay, 50-60 parts of abrasive, 1-7 parts of body toughening material, 0.5-3 parts of recycled material; 0.1-0.8 parts of additive
[0034] The ratio of the mud material to mullite is 1:0.5;
[0035] The water-abrasive material is prepared from the following components in parts by weight: 7.4 parts of water-washed potassium-sodium stone particles, 8.3 parts of water-ground sodium stone powder, 33.3 parts of water-ground medium-temperature sand, 3.7 parts of mortar recycling material, and 47.3 parts of water-ground high-temperature sand;
[0036] The additive is prepared from the following components in parts by weight: 16.1 parts of modified lignin, 48.4 parts of modified bentonite, 32.3 parts of polyvinyl alcohol filament solution, and 3.2 parts of carboxyl cellulose and acrylate copolymer liquid enhancer. In this step, these materials not only ensure product performance, but also contribute to the plasticity and molding of the material in production.
[0037] S2, ball milling powder: the base powder and the spotted powder are ball milled into slurry according to the formula ratio, and the slurry needs to be aged for more than 48 hours. In this step, an efficient stirring equipment is used to ensure that the base powder and the spotted powder are mixed evenly to improve the clarity of the granularity;
[0038] S3, spray drying: The aged green body slurry and spot slurry in the slurry pool are respectively supplied to the spray drying tower through the spray tower slurry pump. The spray drying process requires controlling the spray plate aperture and swirl plate thickness of the spray gun head, and maintaining the temperature in the spray tower to optimize the moisture content and particle size of the powder;
[0039] As a further implementation method, the moisture content of the powder is controlled at 5.5-6.5%, and the outlet temperature needs to be lower than 80°C. In this step, the temperature in the spray tower (380-450°C) and the pressure of the spray tower mud pump (18-22 kg / s) are controlled to optimize the moisture content and fluidity of the powder. The dried powder is screened by a drum screen to ensure that the powder fineness meets the requirements, thereby improving the quality of the pressed green body;
[0040] S4, powder mixing: the spotted powder and the base powder are evenly dispersed, and a powder modifier is added during the mixing process, thereby improving the clarity and fineness of the granularity;
[0041] As a further implementation method, the powder is first passed through a 60-mesh and then a 100-mesh drum screen to ensure uniform mixing. A powder modifier is added during the mixing process to improve the clarity and fineness of the granular feel. In this step, the mixing time is strictly controlled to ensure a reasonable distribution of the powder particle size;
[0042] S5, compression molding: the mixed green body powder is passed through a sieve to ensure that the particle size is uniform and then sent into a press for compression;
[0043] As a further embodiment, the mixed green body powder is passed through a 50-mesh sieve, screened, and sent to a press for pressing and molding. The pressure of the press is 550-560 kg / cm 2 , the speed is 11.5 times / minute. This step avoids the problem of uneven density and cracks of the green body caused by poor pressing, and upgrades the mold to ensure uniform distribution of powder during the pressing process, reducing defects caused by uneven distribution;
[0044] S6, green body drying: the green body after pressing and forming is transported to the drying kiln for drying;
[0045] As a further implementation, a multi-stage temperature-controlled drying kiln is used, with the first four zones at 180°C, the first three zones at 160-170°C, the middle three zones at 135-150°C, and the last three zones at 120°C. The residual moisture of the green body is adjusted to less than 0.5%, and the green body drying strength WEI is 3.5-4.5 MPa. This step can effectively control the drying speed and prevent the body from cracking.
[0046] S7, firing and forming: the dried green body is sent to the calcining kiln for firing.
[0047] As a further implementation method, the firing temperature is controlled at 1178-1193°C, the high-fire insulation time is controlled at 8-12 minutes, and the firing time is controlled at 120-170 minutes. This step adopts advanced kiln technology to ensure uniform temperature distribution in the kiln, improve product consistency and quality stability, thereby ensuring that the rock slab has the required physical and chemical properties.
[0048] Example 1
[0049] The present invention provides a process for preparing a rock plate with clear granularity, comprising the following steps:
[0050] S1. Raw material preparation: transport the mud, mullite, water-abrasive, green body toughening material, recycled material and additives required for the production of rock slabs to the required location according to the proportion;
[0051] S2, ball-milled powder: ball-mill the base powder and the spotted powder into slurry according to the formula ratio, and the slurry needs to be aged for more than 48 hours;
[0052] S3, spray drying: The aged green body slurry and spot slurry in the slurry pool are respectively supplied to the spray drying tower through the spray tower slurry pump. The spray drying process requires controlling the spray plate aperture and swirl plate thickness of the spray gun head, and maintaining the temperature in the spray tower to optimize the moisture content and particle size of the powder;
[0053] S4, powder mixing: the spotted powder and the base powder are evenly dispersed, and a powder modifier is added during the mixing process, thereby improving the clarity and fineness of the granularity;
[0054] S5, compression molding: the mixed green body powder is passed through a sieve to ensure that the particle size is uniform and then sent into a press for compression;
[0055] S6, green body drying: the green body after pressing and forming is transported to the drying kiln for drying;
[0056] S7, firing and forming: the dried green body is sent to the calcining kiln for firing;
[0057] In S1, the clay, mullite, abrasive, green body toughening material, recycled material and additives are prepared from the following components in parts by weight: 35-46.1 parts of clay, 50-60 parts of abrasive, 1-7 parts of green body toughening material, 0.5-3 parts of recycled material; 0.1-0.8 parts of additives
[0058] The ratio of the mud material to mullite is 1:0.5;
[0059] The water-abrasive material is prepared from the following components in parts by weight: 7.4 parts of water-washed potassium-sodium stone particles, 8.3 parts of water-ground sodium stone powder, 33.3 parts of water-ground medium-temperature sand, 3.7 parts of mortar recycling material, and 47.3 parts of water-ground high-temperature sand;
[0060] The additive is prepared from the following components in parts by weight: 16.1 parts of modified lignin, 48.4 parts of modified bentonite, 32.3 parts of polyvinyl alcohol rubber solution, and 3.2 parts of carboxyl cellulose and acrylate copolymer liquid enhancer;
[0061] The flexural strength of the obtained rock slab with clear granularity is 69MPa.
[0062] Example 2
[0063] The difference between Example 2 and Example 1 is that the ratio of mud to mullite in Example 2 is 1:0.4, and the other preparation processes are the same as those in Example 1. The flexural strength of the obtained rock plate with clear granularity is 65 MPa.
[0064] Example 3
[0065] The difference between Example 3 and Example 1 is that the ratio of mud to mullite in Example 3 is 1:0.3, and the other preparation processes are the same as those in Example 1. The flexural strength of the obtained rock plate with clear granularity is 61 MPa.
[0066] Example 4
[0067] The difference between Example 4 and Example 1 is that the ratio of mud to mullite in Example 3 is 1:0.2, and the other preparation processes are the same as those in Example 1. The flexural strength of the obtained rock plate with clear granularity is 56 MPa.
[0068] Example 5
[0069] The difference between Example 5 and Example 1 is that mullite is not added in Example 5, and the other preparation processes are the same as those in Example 1. The flexural strength of the obtained rock plate with clear granularity is 47 MPa.
[0070] Effect evaluation and performance testing
[0071] The flexural strength of Examples 1-5 was tested according to GB / T4100-2015 standard. The test items and results are shown in Table 1 below.
[0072] Table 1 shows the performance test data of the rock slabs in each example
[0073] Flexural strength MPa Example 1 69 Example 2 65 Example 3 61 Example 4 56 Example 5 47
[0074] As described above, the flexural strength of the rock slab obtained in Example 1 is significantly higher than that of Examples 2-5, wherein the flexural strength of the rock slabs of Examples 2-5 is in a decreasing state.
[0075] This is because the content of mullite gradually decreases from Examples 1 to 5. Mullite, as a high-quality aluminum silicate mineral, is widely used in high-performance ceramic materials due to its excellent high-temperature stability and good mechanical properties. In the production of rock slabs, the addition of mullite can not only significantly improve the strength and toughness of the product, but also improve its thermal stability and thermal shock resistance, making it adaptable to more stringent use environments. Therefore, the internal structure of the rock slab with clear granularity obtained by the present invention is more stable, and the clear granularity of the rock slab can be maintained during long-term use.
[0076] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A process for preparing a rock slab with clear granularity, characterized in that: The following steps are involved: S1. Raw material preparation: transport the mud, mullite, water-abrasive, green body toughening material, recycled material and additives required for the production of rock slabs to the required location according to the proportion; S2, ball-milled powder: ball-mill the base powder and the spotted powder into slurry according to the formula ratio, and the slurry needs to be aged for more than 48 hours; S3, spray drying: The aged green body slurry and spot slurry in the slurry pool are respectively supplied to the spray drying tower through the spray tower slurry pump. The spray drying process requires controlling the spray plate aperture and swirl plate thickness of the spray gun head, and maintaining the temperature in the spray tower to optimize the moisture content and particle size of the powder; S4, powder mixing: the spotted powder and the base powder are evenly dispersed, and a powder modifier is added during the mixing process, thereby improving the clarity and fineness of the granularity; S5, compression molding: the mixed green body powder is passed through a sieve to ensure that the particle size is uniform and then sent into a press for compression; S6, green body drying: the green body after pressing and forming is transported to the drying kiln for drying; S7, firing and forming: the dried green body is sent to the calcining kiln for firing.
2. The process for preparing a rock plate with clear granularity according to claim 1, characterized in that: In S1, the clay, mullite, abrasive, green body toughening material, recycled material and additives are prepared from the following components in parts by weight: 35-46.1 parts of clay, 50-60 parts of abrasive, 1-7 parts of green body toughening material, 0.5-3 parts of recycled material; 0.1-0.8 parts of additives The ratio of the mud material to mullite is 1:0.5; The water-abrasive material is prepared from the following components in parts by weight: 7.4 parts of water-washed potassium-sodium stone particles, 8.3 parts of water-ground sodium stone powder, 33.3 parts of water-ground medium-temperature sand, 3.7 parts of mortar recycling material, and 47.3 parts of water-ground high-temperature sand; The additive is prepared from the following components in parts by weight: 16.1 parts of modified lignin, 48.4 parts of modified bentonite, 32.3 parts of polyvinyl alcohol rubber solution, and 3.2 parts of carboxyl cellulose and acrylate copolymer liquid enhancer.
3. The process for preparing a rock plate with clear granularity according to claim 1, characterized in that: In S3, the moisture content of the powder is controlled at 5.5-6.5%, and the outlet temperature needs to be lower than 80°C.
4. The process for preparing a rock plate with clear granularity according to claim 1, characterized in that: In S4, the powder is first passed through a 60-mesh and then a 100-mesh drum screen to ensure uniform mixing.
5. The process for preparing a rock slab with clear granularity according to claim 1, characterized in that: In S4, powder modifiers are added during the mixing process to improve the clarity and fineness of the particles.
6. The process for preparing a rock plate with clear granularity according to claim 1, characterized in that: In S5, the mixed green body powder is passed through a 50-mesh sieve and sent to a press for pressing and molding. The pressure of the press is 550-560kg / cm 2 , speed is 11.5 times / minute.
7. The process for preparing a rock plate with clear granularity according to claim 1, characterized in that: In S6, a multi-stage temperature-controlled drying kiln is used, with the first four zones at 180°C, the first three zones at 160-170°C, the middle three zones at 135-150°C, and the last three zones at 120°C.
8. The process for preparing a rock plate with clear granularity according to claim 1, characterized in that: In S6, the residual moisture of the green body is adjusted to be less than 0.5%, and the dry strength WEI of the green body is 3.5 to 4.5 MPa.
9. The process for preparing a rock plate with clear graininess according to claim 1, characterized in that: In S7, the firing temperature is controlled at 1178-1193°C, the high-fire holding time is controlled at 8-12 minutes, and the firing time is controlled at 120-170 minutes.
Citation Information
Patent Citations
Ceramic rock plate and preparation method thereof
CN111470848A
High-whiteness ceramic tile and production process thereof
CN115259848A
Preparation process of nano rock plate with clear granular sensation and nano rock plate prepared by preparation process
CN115677325A
